2021
DOI: 10.4067/s0716-10182021000600737
|View full text |Cite
|
Sign up to set email alerts
|

Uso ambulatorio de cefalosporinas en una población colombiana: estudio de prescripción-indicación

Abstract: Conflictos de interés: no hubo. Financiamiento: este trabajo de investigación no recibió fuentes de financiación.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In this group of patients, four out of five patients received inappropriate antibiotics. This finding is consistent with other reports [ 11 , 17 , 20 ]. In Canada, Ibrahim et al found that 63.3% of patients did not receive the antimicrobials recommended by management guidelines [ 17 ], while, in the United States, Sutton et al found that among patients who required hospital management, 73.0% did not receive adequate antibiotic management [ 20 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this group of patients, four out of five patients received inappropriate antibiotics. This finding is consistent with other reports [ 11 , 17 , 20 ]. In Canada, Ibrahim et al found that 63.3% of patients did not receive the antimicrobials recommended by management guidelines [ 17 ], while, in the United States, Sutton et al found that among patients who required hospital management, 73.0% did not receive adequate antibiotic management [ 20 ].…”
Section: Discussionsupporting
confidence: 94%
“…In Colombia, several studies on antibiotics in the outpatient setting have found a high proportion of inappropriate prescriptions [ 11 , 21 , 22 , 23 ]. Cephalosporins have been used to treat conditions not indicated in 55.6% of cases [ 11 ], macrolides in 31.3% of cases [ 21 ], fluoroquinolones in 24.0% of cases [ 23 ], and tetracyclines in 23.5% of cases [ 22 ]. This problem has also been described in international studies [ 12 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is common in the literature to find resistance to first-and second-generation cephalosporins, aminopenicillins with beta-lactamase inhibitors, and oxacillin, among others. [14][15][16] In Colombia, the use of antibiotics for unapproved indications is common, [29][30][31] a condition that leads to adverse clinical (increased length of hospital stay, morbidity, mortality, and antimicrobial resistance) and economic (increased costs of care) effects. 32 Thus, it is important to highlight that, in this study, the inappropriate use of antibiotics prevailed in most patients.…”
Section: Discussionmentioning
confidence: 99%
“…In Colombia, the use of antibiotics for unapproved indications is common, 2931 a condition that leads to adverse clinical (increased length of hospital stay, morbidity, mortality, and antimicrobial resistance) and economic (increased costs of care) effects. 32 Thus, it is important to highlight that, in this study, the inappropriate use of antibiotics prevailed in most patients.…”
Section: Discussionmentioning
confidence: 99%